2017
DOI: 10.1021/acs.jafc.7b01380
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Processing of Broccoli Sprouts: Influence on Bioactivation of Glucosinolates to Isothiocyanates

Abstract: Effects of high-pressure processing (HPP, 100-600 MPa for 3 min at 30 °C) on the glucosinolate content, conversion to isothiocyanates, and color changes during storage in fresh broccoli sprouts were investigated. A mild heat treatment (60 °C) and boiling (100 °C) were used as positive and negative controls, respectively. Glucosinolates were quantified using liquid chromatography-mass spectrometry, and isothiocyanates were quantified using high-performance liquid chromatography-photodiode array detection. A for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…It has also been shown that isothiocyanates in broccoli juice are relatively thermolabile and pressure stable . In addition, high pressure processing (HPP) caused no negative effects on the glucosinolate–myrosinase system in broccoli sprouts …”
Section: Chemistry Bioavailability and Metabolism Of Cruciferous Vementioning
confidence: 99%
“…It has also been shown that isothiocyanates in broccoli juice are relatively thermolabile and pressure stable . In addition, high pressure processing (HPP) caused no negative effects on the glucosinolate–myrosinase system in broccoli sprouts …”
Section: Chemistry Bioavailability and Metabolism Of Cruciferous Vementioning
confidence: 99%
“…The advantage is that it affords the opportunity to selectively inactivate certain enzymes while retaining other enzymes such as MYR, and ruptures cell membranes to allow the GLs to come into contact with MYR . High‐pressure treated broccoli (600 MPa for 3 min at 30 °C) contained a 6‐fold higher ITC concentration compared to the untreated samples . Another new technology is pulse electric field processing.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…* * [42,57,65] High pressure n.a. ↓↑ ↓↑ [41,[66][67][68][69][70]107,108] Pulsed electric field n.i. n.i.…”
Section: Domestic or Industrial Treatment Leaching Myr Gls Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…High-Pressure Processing has been used in many fields of food industry, such as fruit products [2], seafood (Teixeira et al, 2013), vegetables [3], but it was often treated without exogenous enzyme, so the shape of fish needs a long time (1 or 2 months) to degrade into small fragments [4].…”
Section: Introductionmentioning
confidence: 99%